SERVICE QUALITY, BRAND TRUST, AND BRAND LOYALTY - Ana Mariana; Bram Hadianto; Catherine Suyanto (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study plans to investigate and analyze the influence of service quality on brand trust and brand trust on brand loyalty by utilizing the Precious One users as the object and population. Based on this goal, this study is designed quantitatively; thus, we grab the samples by simple random sampling. According to the Isaac and Michael formula, the total pieces should be 344. However, 251 users respond to filling the questionnaire; hence, the participating rate is 75.45%. Moreover, we use confirmatory factor analysis to validate the responses, the Cronbach Alpha analysis to test response reliability, and the structural equation model based on covariance to examine the related hypotheses. Overall, we find that service quality positively affects brand trust. Also, this positive sign is available in the causal relationship between brand trust and brand loyalty. Hence, the service quality is vital for Precious One to commit to building brand trust, creating brand loyalty.